2006
DOI: 10.1038/sj.bjc.6603385
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of Tiam1 protein expression in prostate carcinomas

Abstract: The Rac-specific guanine nucleotide exchange factor, Tiam1, plays a major role in oncogenicity, tumour invasion and metastasis but its usefulness as a prognostic marker in human cancer has not been tested yet. In the present study, Tiam1 expression was analysed in benign secretory epithelium, pre-neoplastic high-grade prostatic intraepithelium neoplasia (HG-PIN) and prostate carcinomas of 60 R0-resected radical prostatectomy specimens by semiquantitative immunohistochemistry. Tiam1 proved significantly overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
71
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 25 publications
3
71
1
Order By: Relevance
“…Repression of Rac1 activity by NSC23766 diminished Rac-dependent cell proliferation of PC3 prostate cancer line (36) and leukemia cell lines both in vitro and in vivo (37)(38)(39)(40); it also inhibited cell migration of several breast cancer cell lines (41) and induced apoptosis in leukemia (37)(38)(39)(40) and glioma (42) cell lines. Increasing evidence shows that Tiam1 and Trio are overexpressed in different types of human tumors (18)(19)(20), including human breast (42) carcinomas, which is believed to contribute to Rac1 hyperactivity. This promoted us to investigate whether targeting Rac1 could be beneficial in eliminating cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repression of Rac1 activity by NSC23766 diminished Rac-dependent cell proliferation of PC3 prostate cancer line (36) and leukemia cell lines both in vitro and in vivo (37)(38)(39)(40); it also inhibited cell migration of several breast cancer cell lines (41) and induced apoptosis in leukemia (37)(38)(39)(40) and glioma (42) cell lines. Increasing evidence shows that Tiam1 and Trio are overexpressed in different types of human tumors (18)(19)(20), including human breast (42) carcinomas, which is believed to contribute to Rac1 hyperactivity. This promoted us to investigate whether targeting Rac1 could be beneficial in eliminating cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, NF-κB activation is known to induce transcription of its target genes such as cyclin D1, Bcl-2, and Bcl-XL. In human cancers, Rac1 is found to be frequently hyperactivated due to elevated protein expression in itself (16,17) or alteration in its regulatory proteins (18)(19)(20). The dysregulated Rac1 activity has been implicated in several aspects of malignant phenotypes such as tumorigenic transformation and outgrowth (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several reports have indicated that the high expression of Tiam1 is significantly associated with the shortened survival of patients with malignancies. For example, Engers et al reported that high Tiam1 expression is an independent predictor of decreased disease-free survival for patients with prostate cancer (16). Yang et al demonstrated that the high expression of Tiam1 correlates with a poor prognosis in hepatocellular carcinoma (29).…”
mentioning
confidence: 99%
“…Tiam1 is a potent modifier of oncogenic Ras-induced skin tumor initiation, promotion and progression (13). Moreover, numerous studies have demonstrated that the upregulation of Tiam1 is associated with an aggressive phenotype and a poor clinical outcome in several types of malignant tumors, including breast (14), colon (15), prostate (16), liver (17) and nasopharyngeal (11) esophageal squamous cell carcinoma (18). However, to date, the correlation between Tiam1 expression and ovarian carcinoma has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Tiam1 was first discovered in a proviral insertion mutation study, and isolated and identified in the highly aggressive mice T lymphoma cells variants, also called T-cell lymphoma invasion and metastasis-inducing factor 1 (Tiam1) (Fleming et al, 2000;Engers et al, 2006;Li et al, 2011;Chen et al, 2012). The chemical component protein serves as a guanylic acid transfer factor, which can transform the guanylic acid bisphosphate into guanylic acid triphosphoric acid and promote guanylic acid bisphosphate release and binding to guanylic acid triphosphoric acid.…”
Section: Introductionmentioning
confidence: 99%